Extended spectrum beta-lactamases (ESBL) in Escherichia coli and Klebsiella pneumoniae: trends in the hospital and community settings - Khanfar, Husam S.; Bindayna, Khalid M.; Senok, Abiola C.; Botta, Giuseppe A. (The Journal of Infection in Developing Countries, 2009)
Background: To assess the prevalence of extended spectrum beta-lactamase (ESBL) producing Escherichia coli and Klebsiella strains in nosocomial and community-acquired infections.Methodology: The study was conducted at a centralized microbiology laboratory in the Eastern Province of Saudi Arabia. Laboratory records (January 2004 - December 2005) were assessed. Associated resistance to a panel of antibiotics was determined.Results: A total of 6,750 Gram-negative organisms were assessed for ESBL-phenotype. ESBL was detected in 6% (409/6,750) of isolates, the majority of which were E. coli (83%). ESBL producers were significantly higher among isolates from in-patients 15.4% (143/927) versus out-patients (4.5%; 266/5,823); p < 0.05. Old age (older than 60 years) represented a significant risk for having an ESBL-producing pathogen. Urine was the major source of ESBL isolates in in-patients (46.1%) and out-patients (74.4%). The proportion of urinary E. coli isolates which were ESBL producers was significantly higher among in-patients (53/506; 10.4%) compared to out-patients (182/4,074; 4.4%); p<0.05. Among in-patients, 60% of the ESBL associated infections were nosocomial. All were sensitive to imipenem but high levels of resistance to gentamicin, amikacin, amoxicillin-clavulanic acid and ciprofloxacin was shown.Conclusion: The findings document evidence of the spread of multiresistant ESBL-producers into the community. This has significant implications for patient management, and indicates the need for increased surveillance and molecular characterization of these isolates.